C/BCN core/shell nanotube films with improved thermoelectric properties. (November 2016) - Chiang, Wei-Hung; Hsieh, Cheng-Yu; Lo, Shen-Chuan; Chang, Yu-Chen; Kawai, Tsuyoshi; Nonoguchi, Yoshiyuki
Abstract: A proof-of-concept of the enhancement in thermoelectric properties using C/BCN core/shell nanotube heterojunctions has been reported. We demonstrated a scalable two-step reaction route to produce C/BCN core/shell nanotubes with bulk quantities. Systematic X-ray photoelectron spectroscopy (XPS) and atomic-scale high-resolution transmission electron microscope electron energy loss spectroscopy (HRTEM-EELS) characterizations indicate that the synthetic heterostructures with CNT core and BCN shell can be prepared by the developed method. Thermoelectric property measurements revealed that moderate BCN shell effectively improves the Seebeck coefficient, leading to a 6.4-fold increase in thermoelectric power factor of 0.64 μW/mK 2 . Our study provides a fundamental understanding for the rational design of nanostructured heterojunctions for improved thermoelectric properties of carbon-based materials.